ALAT TEPAT GUNA UNTUK PEMBUATAN LOGO PADA PROSES PEMBUATAN SEPATU UNTUK INDUSTRI KECIL - Aris Budianto (Politeknik ATK Yogyakarta, 2013)
Shoes in addition to those known from the model are also of the designation. Shoes are known not only as described above, but because of the following trademark or logo. The logo can be made by embossed. The authors in this study chose the title